A new species of grenadier, genus Macrourus (Teleostei, Gadiformes, Macrouridae) from the southern hemisphere and a revision of the genus - Mcmillan, Peter; Iwamoto, Tomio; Stewart, Andrew; Smith, Peter J. (Zootaxa, 2012)
A new Macrourus species from the southern hemisphere is described. It was first recognised from the Ross Sea, Antarcticaafter specimens sampled during the International Polar Year in 2008 showed significant genetic differences (C01) amongthose initially identified as M. whitsoni (Regan). M. caml sp. nov. has 8 (rarely 7 or 9) pelvic fin rays, a band (2–3 rows)of small uniform-sized teeth in the lower jaw, lacks an outer row of enlarged teeth in the upper jaw, 30–40 scales in a di-agonal row from anal fin origin to lateral line, ventral surface of the head is mostly scaled, except for scaleless areas an-terior to the mouth and on the anterior half of the lower jaw. M caml sp. nov. is large, reaching at least 890 mm TL andappears to be abundant. Numerous specimens caught by commercial bottom longline vessels fishing in the Ross Sea areheld at Museum of New Zealand Te Papa Tongarewa, Wellington New Zealand. All five species of Macrourus (M. ber-glax, M. caml, M. carinatus, M. holotrachys, and M. whitsoni) are compared and illustrated, based on examination of specimens, and a key to species is provided.